Under-utilization of Narrow-Spectrum Antibiotics in the Ambulatory Management of Pediatric UTI: A Single-Center Experience - Lee, Philip; Kim, Mimi; Herold, Betsy C.; Soma, Vijaya L. (Frontiers in Pediatrics, 2021)
Objective: There are urinary tract infection (UTI) guidelines for treatment of patients <2 years old, but there is a paucity of data for other pediatric age groups including the potential role for stewardship to reduce prescription of broad-spectrum antibiotics. We assessed practice patterns for the diagnosis and empiric treatment of UTI for outpatient and school health sites affiliated with a large urban pediatric medical center. We hypothesized that outpatient providers under-utilize narrow-spectrum antibiotics, such as first-generation cephalosporins, for uncomplicated UTI. Study Design: Retrospective study from December 1st, 2015 to May 31st, 2016 Results: The study population included 903 children (70.1% female) with a median age of 11 years, evaluated in an outpatient clinic (n=780, 86.4%) or school health site (n=123, 13.6%). E. coli was the most common urinary pathogen (50.9%) and 92.6% of E. coli isolates were susceptible to cephalexin. However, cephalexin was prescribed empirically for only 12.8% of patients. In contrast, sulfamethoxazole-trimethoprim was commonly prescribed, but only 79% of E. coli isolates were susceptible. Antibiotics were discontinued in only 3 of 48 children who had negative urine cultures. Conclusions: Cephalexin may be the most appropriate first-line choice for management of outpatient UTI for our patient population. Antibiotics were rarely discontinued for those with negative urine cultures. Antibiotic stewardship in the outpatient setting could reduce unnecessary antibiotic exposure in the management of pediatric UTI.